2011
DOI: 10.1007/s11665-010-9797-8
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Element Simulation of the Anti-Buckling-Effect of a Shape Memory Alloy Bar

Abstract: Shape memory alloys (SMA) are characterized by an intricate stress-strain curve modified by temperature, posing thermomechanically coupled problems. A model able to address this feature is the Mü ller-Achenbach-Seelecke (MAS) model which had been ported into the user material interface in the finite-element (FEM) simulation software ABAQUS. The literature on this model mainly focuses on pseudo-elasticity of SMA at elevated temperature. We address a numerical investigation in the low-temperature pseudo-plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…They concluded that the transformation of typical SMA phases affected the solution to the problem. Finally, Richter et al [41] numerically analyzed the phenomenon so-called anti-buckling effect reported by Urushiyama et al [42] Table 1 shows the list of tests with the number of test speci-239 mens, the total bar length L total , the free length of each test L and mechanical slenderness L=k (where k ¼ D=4 and D is the bar diameter). A total of 30 steel bars and 6 Ni-Ti bars were tested.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the transformation of typical SMA phases affected the solution to the problem. Finally, Richter et al [41] numerically analyzed the phenomenon so-called anti-buckling effect reported by Urushiyama et al [42] Table 1 shows the list of tests with the number of test speci-239 mens, the total bar length L total , the free length of each test L and mechanical slenderness L=k (where k ¼ D=4 and D is the bar diameter). A total of 30 steel bars and 6 Ni-Ti bars were tested.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the initial pre-strain, the trends of the stressstrain diagram during loading in tension and compression are not the same (Richter et al, 2010). Therefore, after complete removal of the bending moment, the SME beam-column remains deflected and inhomogeneous stress distribution across the cross section occurs (Figure 3(e)).…”
Section: Td-effect On Sme Beam-columnsmentioning
confidence: 99%
“…In the latter, the deformed shape of the structures can be recovered by applying axially compressive load; it is named ''Twinning Deformation effect'' (TD-effect) by Urushiyama et al (2003). The origin of this effect roots in the inhomogeneous stress states and mechanically induced twin-twin phase transformations (Richter et al, 2010;Urushiyama et al, 2003;Watkins and Shaw, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It (a) Balloon inflation (adapted from [Alexander 1971]) (b) Sheet wrinkling in tension (adapted from [Nayyar et al 2014]) (c) Martensitic SMA column straightening (adapted from [Urushiyama et al 2003]) should also be noted that the mechanical behavior of SMAs in the martensite phase differs from that of superelastic SMAs (which are examined here), although both exhibit the seemingly necessary stiffening at large strains for unbuckling to occur. As a follow-up to this work, Richter et al (2011) used a finite element model to capture the behavior of SMA columns in the martensite phase, successfully simulating this straightening behavior during compression.…”
Section: Introductionmentioning
confidence: 99%